Length and Width of The Foramen Magnum of Dry Ossified Human Occipital Bone (Bangladesh Journal of Anatomy, 2016)
Context : Some important vital neuroanatomical structures such as cervical part of spinal cord, vertebral arteries, nerves and meninges passes through the foramen magnum. Morphometric data of foramen magnum is essential for anthropologists and neurosurgeons for various surgical diagnosis and treatment. Materials and Methods : A cross- sectional analytic type of study was conducted in the Department of Anatomy, Dhaka Medical College, Dhaka from January 2011 to December 2011. The length and width of foramen magnum were measured with the help of digital slide calipers. Results : The mean ± SD length of foramen magnum was greater in male than mean ± SD length of foramen magnum in female (p